2020
DOI: 10.1155/2020/8508547
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Study of Tetanus Patients in Fujian Province of China: A Retrospective Review of 95 Cases

Abstract: Background. Tetanus is a life-threatening disease in developing countries and is accompanied by a high mortality rate. Although China is the world’s largest developing country, there have been few clinical studies on tetanus in China. The purpose of this study was to investigate the epidemiology, incidence, and management of tetanus in Fujian Province and to understand the current treatment and prognosis of tetanus patients. Methods. This was a retrospective, multicenter observational study of patients who pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 13 publications
3
9
0
Order By: Relevance
“…Hence it is considered to be less suitable for prognostic stratification. Nevertheless, similar to other studies [ 22 ], we noted that nearly 50% of patients presented with severe and very severe disease.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Hence it is considered to be less suitable for prognostic stratification. Nevertheless, similar to other studies [ 22 ], we noted that nearly 50% of patients presented with severe and very severe disease.…”
Section: Discussionsupporting
confidence: 91%
“…One important finding of our study is that more than half of the patients were farmers and lived in rural areas. Similarly, many previous studies [ 16 , 19 22 ] observed a high proportion of farmers among tetanus patients. As C .…”
Section: Discussionsupporting
confidence: 64%
“…C. tetani is susceptible to several antimicrobials: penicillins, cephalosporins, metronidazole, macrolides, tetracyclines, and imipenem [21][22][23] . It is recommended that specific antimicrobial therapy should be given with one of these modalities: per os or IV metronidazole (< 7 days of age, 15 mg/kg/day in divided doses; > 7 days, 30 mg/kg/day in divided doses, for 10-14 days); or IV penicillin G (100,000 U/kg/day administered at 6-hour intervals, for 10-14 days).…”
Section: ) Eradication Of C Tetanimentioning
confidence: 99%
“…Clinical experience has demonstrated that mortality rate was lowest in those treated with combined therapy of diazepam, phenobarbital sodium, and/or chlorpromazine 21) . Omphalectomy has also been used to eliminate the toxin production 21) .…”
Section: ) Sedation and Neuromuscular Blockadementioning
confidence: 99%
“…The disease is mediated by spores that enter the human body on contact with broken skin or mucosa. Once in an anaerobic environment within the body, the spores produce tetanospasmin, the tetanus neurotoxin responsible for the associated symptoms: muscle spasms, stiffness, fever, muscle aches, and dysphagia, among others [1] .…”
Section: Introductionmentioning
confidence: 99%